Calling in retirement: A mixed methods study. Issue 4 (4th July 2017) - Duffy, Ryan D.; Torrey, Carrie L.; England, Jessica; Tebbe, Elliot A.
Abstract: This mixed methods study aimed to examine the experiences of a calling in retirement with a sample of 196 retired adults. First, a qualitative analysis explored the types of activities participants experienced as a calling as well as the types of barriers that participants perceived as keeping them from living their calling. 'Helping Others' emerged as the largest category of calling that participants endorsed and 'No Resources to Live Calling' emerged as the most frequently endorsed barrier. Building on our qualitative findings, we conducted a quantitative analysis to examine the relation of perceiving a calling with well-being. Consistent with prior research with working adult populations and in support of our hypotheses, perceiving a calling related to life meaning and life satisfaction, and structural equation modeling demonstrated that life meaning and living a calling (via life meaning) fully mediated the perceiving calling–life satisfaction relation. Implications for research and practice are discussed.